Determinan Minat Masyarakat Desa Airgegas Kebupaten Bangka Selatan Menabung di Bank Syariah - Findriyani, Ella; Wulpiah, Wulpiah; Nurdin, Muhamad (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2024)
The development of Islamic banking is still not widely known by the majority of the public. This is due to the insufficient outreach efforts made by Islamic banking institutions. Consequently, the public lacks understanding about Islamic banking products, and there is a need to capture the attention of the residents of Airgegas village or motivate them by addressing the factors that influence their decision to choose Islamic banking services, which include knowledge and motivation. This research aims to identify the determining factors of interest in saving, specifically knowledge and motivation, among the residents of Airgegas Village in South Bangka Regency in saving at Islamic banks. This research employs a quantitative approach. The population in this study consists of 4,786 individuals, with the sample selection technique being simple random sampling. The sample size was determined using the Slovin formula, resulting in 98 respondents. Data processing was conducted using SPSS version 26. The results of this study indicate that the knowledge variable (X1) influences the interest of the residents of Airgegas Village in saving at Islamic banks (Y) with a t-value of 9.699 > t-table value of 1.985. Furthermore, the motivation variable (X2) influences the interest of the residents of Airgegas Village in saving at Islamic banks (Y) with a t-value of 2.592 > t-table value of 1.985. Simultaneously, the knowledge (X1) and motivation (X2) variables have a positive influence, with an F-value of 109.714 > F-table value of 3.09, thus H0 is rejected and Ha is accepted. Therefore, both variables together have a positive and significant effect on the interest of the residents of Airgegas Village in saving at Islamic banks.